Megaptera novaeangliae - James G. Mead; Robert L. Brownell, Jr. (Smithsonian Institution Press, 1993)
Megaptera novaeangliae (Borowski, 1781). Gemein. Naturgesch. Thier., 2(1):21. TYPE LOCALITY: USA, "de la nouvelle Angleterre " (= coast of New England). DISTRIBUTION: Worldwide: cold-temperate to tropical waters. STATUS: CITES - Appendix I; U.S. ESA - Endangered; IUCN - Vulnerable. SYNONYMS: braziliensis, burmeisteri, lalandii, longimana, longipinna, nodosa, versabilis. COMMENTS: Reviewed by Winn and Reichley (1985). Published as part of James G. Mead & Robert L. Brownell, Jr., 1993, Order Cetacea, pp. 349-364 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 350, DOI: 10.5281/zenodo.7352970